The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acs.jpcc.9b07885
|View full text |Cite
|
Sign up to set email alerts
|

Fast Oxygen Transport in Bottlelike Channels for Y-Doped BaZrO3: A Reactive Molecular Dynamics Investigation

Abstract: Yttrium-doped barium zirconate (BZY) has emerged as an attractive candidate of oxygen ion (O2–) conducting solid electrolyte because of its high ionic conductivity and excellent chemical stability. In this work, the O2– transport properties and mechanisms of BZY coexisting oxygen vacancies, dopants, and edge dislocations are simulated by reactive molecular dynamics for the first time, and the yttrium concentration (Y%) and temperature (T) dependences of thermodynamic and kinetic properties are studied for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…From experiment, T iso may be determined by computational simulations. [52] For proton conductivity in perovskites, some other simple descriptors, such as ionic radii and basicity, are already known. Very likely, these descriptors turn out to be included in the concept of proton-phonon interaction.…”
Section: Tuning the Isokinetic Temperature According To Mnrmentioning
confidence: 99%
“…From experiment, T iso may be determined by computational simulations. [52] For proton conductivity in perovskites, some other simple descriptors, such as ionic radii and basicity, are already known. Very likely, these descriptors turn out to be included in the concept of proton-phonon interaction.…”
Section: Tuning the Isokinetic Temperature According To Mnrmentioning
confidence: 99%
“…Through incorporating reactive force eld potentials, the oxygen vacancies, doping effect, and edge dislocations have been explored for the BZO system with or without edge dislocations, and calculations on radial distribution function, expansion coe cient, and ionic self-diffusion coe cient. The MD calculations on the aforementioned entities have been carried out employing the dependencies of temperature and doping percentage [186]. These results manifest that a mole fraction of yttrium can increase oxygen transport which can be characterized by the oxygen transport coe cient.…”
Section: Studiesmentioning
confidence: 92%
“…Although less numerous, similar studies have been conducted to determine the effects of dislocations on ionic transport in BaZrO 3 (BZO). For BZO, two experimental studies, both on BZO thin-films on NdGaO 3 substrates, showed significant increases in proton conductivity as a result of misfit dislocations that form due to the lattice mismatch between BZO and NdGaO 3 . , Although the authors found similar results, the explanations they proposed are different. Felici et al .…”
Section: Effects Of Dislocations On Transportmentioning
confidence: 99%
“…determined that the effect was due to the incorporation of hydroxyl groups at dislocations, which required protons to be integrated to provide charge balance, whereas Liu et al . proposed that the increase in both barium and oxygen vacancies could have enabled the higher conductivity. , For oxygen diffusion in these systems, simulations by Li et al propose pipe diffusion as the mechanism, so the explanations for dislocation-modified transport can vary greatly based on the study, carrier in question, processing route, including impurity incorporation (if experimental), and types of dislocations present . For a simplified summary of reported effects of dislocations on transport in oxides, where diffusivity or conductivity was directly measured or simulated, refer to Table .…”
Section: Effects Of Dislocations On Transportmentioning
confidence: 99%
See 1 more Smart Citation